Le vélo à assistance électrique, enjeux d'une pratique en plein essor. - Marincek, Dimitri (Verband der Schweizer Geographen, 2018)
The development of electric-assisted bicycles (e-bikes) raises three broad categories of challenges for research and practice. The first is its adoption by new users, which raises questions about how new mobility practices diffuse and are constituted throughout the life course. The second relates to the potential for modal substitution of cars by e-bikes, and the infrastructure this requires. The third challenge is that of public policy, of how to accompany the e-bike's sales growth and which role to give it in the transport system.
Keywords: Individualverkehr; Fahrradverkehr; Elektromobilität; E-Bike; Pedelec